Coxsackie Virus B(4) Pericarditis in Mice - Tsui, Ching-Ya (1971)
The pericardium of hearts of 200 mice inoculated i.p. with Coxsackie virus B(4) was studied by histological and direct immunofluorescent techniques. The findings of pericarditis and positive immunofluorescent staining in the pericardial epithelium are described and the pathogenesis and natural history of Coxsackie viral pericarditis in mice are discussed. Coxsackie viral pericarditis can be easily produced experimentally in mice, providing an opportunity to study the natural history of pericarditis of viral aetiology and the possible sequel chronic relapsing or constrictive pericarditis seen in man.